2017
DOI: 10.1016/j.msec.2017.03.232
|View full text |Cite
|
Sign up to set email alerts
|

The repairing of full-thickness skin deficiency and its biological mechanism using decellularized human amniotic membrane as the wound dressing

Abstract: Human amniotic membrane (HAM) was a biocompatible scaffold with advantages of anti-inflammatory, low antigen, feasibility, tolerance and low cost. In our previous work, HAM was treated to be decellularized using surfactant, lipase and DNAase methods and the efficacy as an implantable biological mesh was verified after decellularization treatment. In this work, we used the previous protocol to decellularize the fresh HAM, and applied it to repair full-thickness skin defects with Sprague-Dawley rats as the test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 27 publications
1
41
0
1
Order By: Relevance
“…In particular, acellular amniotic membrane was investigated as a scaffold to support/deliver epithelial cells [240], limbal stem cells [296], human adipose stem cells [297], differentiated neural-like cells [298], mice ovarian follicular culture [299], as well as a scaffold with cell-guiding ability [300] but it may also be used as a surgical patch/mesh [301] for reconstruction of vessels [302] (also once rolled up [303,304]); bladder [305] or circumferential urethral defect [306], reconstruction of esophageal wall [307], cardiac [120,308] and cerebrospinal fluid [308] applications, endometrial fibrosis treatment [309], soft tissue damage, limbal stem cell deficiency [293], skin defects also due to ulcers or severe skin burns or for corneal defects [310,311,312], treatment of pharyngocutaneous fistula after total laryngectomy [291], and for fetoscopic closure of iatrogenic defects in fetal membranes [313].…”
Section: Products Of Childbirth: Umbilical Cord Placenta and Amnmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, acellular amniotic membrane was investigated as a scaffold to support/deliver epithelial cells [240], limbal stem cells [296], human adipose stem cells [297], differentiated neural-like cells [298], mice ovarian follicular culture [299], as well as a scaffold with cell-guiding ability [300] but it may also be used as a surgical patch/mesh [301] for reconstruction of vessels [302] (also once rolled up [303,304]); bladder [305] or circumferential urethral defect [306], reconstruction of esophageal wall [307], cardiac [120,308] and cerebrospinal fluid [308] applications, endometrial fibrosis treatment [309], soft tissue damage, limbal stem cell deficiency [293], skin defects also due to ulcers or severe skin burns or for corneal defects [310,311,312], treatment of pharyngocutaneous fistula after total laryngectomy [291], and for fetoscopic closure of iatrogenic defects in fetal membranes [313].…”
Section: Products Of Childbirth: Umbilical Cord Placenta and Amnmentioning
confidence: 99%
“…The in vivo behavior of AM-derived scaffolds was evaluated in: rat model of intrauterine adhesion [306]; third-degree skin burns in BALB/c mice [312]; full-thickness skin defects in Sprague Dawley rats [310]; patients experiencing pharyngocutaneous fistula because of surgical treatment of laryngeal squamous cell carcinoma [291]; BALB/c mice in which myocardial infarction was induced [319]; uterus of rabbits [301]; subcutaneously in the left hemiback of rats [316]; in the left pulmonary artery of pig after a left posterolateral thoracotomy [302]; in dogs urethral defect model [306]; for closure of fetoscopic entry wounds in the exposed rabbit amniotic sac [313]; and deep flexor tendon of the chicken toe [320].…”
Section: Products Of Childbirth: Umbilical Cord Placenta and Amnmentioning
confidence: 99%
“…Among the many processes available for creating 3D environments, the most successful ones are summarized in the following section. Special mention goes to 3D bioprinting [212][213][214][215] and decellularized scaffolds [216][217][218], which offer promising potential in terms of signalling modulation and biomimetism. In terms of macrodimensionality, 3D additive manufacturing techniques represent some of the most promising and flexible methods to process artificial skin tissue for wounds because of their versatility, reproducibility and low-cost [219,220].…”
Section: Physical Signalingmentioning
confidence: 99%
“…In this study, the high expression of TGF-β1 on POD 7 is considered to reflect the migration of M2 macrophages that exert a powerful anti-inflammatory effect to reduce and terminate the inflammatory response. It has been reported that the AM significantly increases growth factors early in wound healing but acts to suppress it later [ 58 ]. Since IL-10 remains in HD-AM, it is considered to exhibit the same action as fresh or cryopreserved AM.…”
Section: Discussionmentioning
confidence: 99%